Paradigma Riset Integratif pada Pesantren Riset Al-Khawarizmi - Dina Sabila Sarofina; Endhin Rahma Mufidha; Siti Faikhatul Hikmah; Zidni Rosyidah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research explores the integrative paradigm of research-based Islamic boarding schools, focusing on Al-Khawarizmi Research Pesantren in Mijen, Semarang. Utilizing a qualitative approach with direct interviews, the study investigates how pesantren can bridge traditional Islamic education and modern scientific research. The findings reveal three key dimensions: a critical philosophical approach, integration of traditional-modern scientific knowledge, and multicultural value internalization. The research demonstrates how pesantren can develop critical thinking, research skills, and social awareness among students through an innovative educational model that combines religious learning, research methodology, and cross-cultural collaboration. The study contributes to understanding the potential of pesantren as dynamic educational institutions capable of responding to contemporary challenges while maintaining their core traditional values.